AKIBAT HUKUM BAGI NARAPIDANA YANG MELAKUKAN TINDAK KEJAHATAN DI DALAM LEMBAGA PEMASYARAKATAN KELAS IIA KUPANG SERTA UPAYA PENANGGULANGANNYA - Hida, Dian J. A; Leo, Rudepel Petrus; Amalo, Heryanto (Petitum Law Journal, 2023)
The Criminal Code (KUHP) regulates the sanctions that will be received if a crime is committed. Persecution is regulated in Articles 351 to 356 of the Criminal Code. The provisions of these articles regulate ordinary abuse, light abuse, planned abuse, serious abuse, planned serious abuse, and abuse of people of certain qualities as well as abuse in the form of participating in attacks or fights. regarding abuse between prisoners, especially in relation to legal sanctions, the author is interested in studying this matter more by conducting research for writing a thesis entitled